PENEGAKKAN HUKUM TERHADAP PELAKU PENGGELAPAN UANG SETORAN DI PT. NIPSEA PAINT AND CHEMICALE CABANG BANDAR LAMPUNG(Studi Putusan Nomor : 527/Pid.B/2023/PN.Tjk) - Nadira Nadira; I Ketut Seregig, Yulia Hesti (JOURNAL OF LAW AND NATION, 2024)
Law enforcement is related to the notion of "law enforcement" in the narrow word, and the notion of justice in the broad sense is substantive law, namely the upholding of justice. Criminal prosecution means an effort to make law a guideline, both in a narrow formal sense as well as in a broader substantive sense. The research uses a normative legal approach as well as an empirical legal approach. the data source used is secondary data and the type of data used includes secondary data, tersier data and primary data. The process of data analysis is described and analyzed qualitatively, The process of data analysis is described and analyzed qualitatively, and the results of the analysis are interpreted in the form of deductive conclusions, namely answers to problems according to research results. according to the results of the research and discussion that have been presented, the authors are of the opinion that the imposition of a prison sentence of 1 year and 6 months on the defendant is appropriate using the crime committed by the defendant in such a way as a result of which it can cause a deterrent effect. Of course, when deciding on a case, the judge will consider information such as testimony from witnesses and the accused to state what actually happened, the existence of evidence supporting the judge's consideration in imposing sanctions on the defendant, as well as the existence of aggravating and mitigating factors. element. So, the judge also weighed in accordance with Article 374 of the Criminal Code on the crime of embezzlement of office.